Biomechanics of implant-supported restorations - De Andrade, Guilherme Schmitt; Kalman, Les; Giudice, Roberto Lo; Adolfi, Dario [UNESP]; Feilzer, Albert J.; Tribst, João Paulo Mendes (Editora Cubo, 2023)
The rehabilitation of patients with dental implant-supported restorations is an ideal treatment option in contemporary dentistry. The aim of this review was to compile and to demonstrate the mechanical response during loading condition, on the stress distributions of implant-supported prostheses. The findings show that the majority of stresses were concentrated in the cervical region of the implant/abutment interface and that they can be affected by several clinical parameters and loading conditions. Finally, the final prosthetic design should combine superior mechanical response, long-term survival rate and allow patient satisfaction.
Biomecânica das restaurações implantossuportadas
Keywords: Biomechanics; Dental Implants; Finite element analysis; Prostheses and Implants; Review